New Figurations in Architecture Theory: From Queer Performance to Becoming Trans - Robert Alexander Gorny; Dirk van den Heuvel (Footprint)
The editorial introduction to this Footprint issue maps some of the latest developments in the field of queer studies and the realm of architecture and urban design. The aim is for a productive exhange between the fields since queer theory can be instrumental in moving beyond the heteronormative dominance in architectural thinking, which is characterized by an essentialist approach based on binary notions, rather than an understanding of architecture as an interface in material processes of becoming and producing differences. After a brief discussion of the history of exchanges between queer studies and architectural history and theory, the authors propose to complement the notion of queering with the new developments in the field of trans studies, which propose to rethink architecture in terms of a materialist understanding of buildings as bodies which are in a constant flux of change and becoming instead of fixed and stable objects or identities.